The Impact of Structural Competence towards Speaking Competence of the Fourth Semester Students of English Department - Muhammad Nafi Annury (UIN Salatiga, 2013)
This paper tries to define any impact of structural competence towards speaking competence. In this research, the writer used descriptive co-relational method. It was used to describe whether there was an impact between two variables, i.e. structural competence (X) as independent variable and speaking competence (Y) as dependent variable. The subject of study was the fourth semester students of English department of Tarbiyah Faculty IAIN Walisongo Semarang. After the data had been analyzed, it was found that there was significant impact of structural competence especially in appropriateness. It helped students to arrange words into sentences that they utter. Keywords :Structural Competence; Speaking Competence